Pilot Testing a Nutrition and Motivational Interviewing Curriculum for Undergraduate Nursing Students (P04-174-19). (13th June 2019) - Berlinsky, Taylor; Moore, Amy; Martins, Diane; DiBiasio, Lisa; Tovar, Alison
Abstract: Objectives: To develop a childhood obesity prevention curriculum for undergraduate nursing students and test the initial feasibility and efficacy to increase: 1) participants' knowledge about motivational interviewing (MI) and health behaviors associated with obesity, and 2) participants' self-efficacy and ability to apply knowledge to conduct MI and discuss health behaviors related to childhood obesity. Methods: Nutrition and nursing professionals developed the curriculum, which was taught in three 2.5-hour sessions with one follow-up session. Using a non-experimental pre-post study design, knowledge, self-efficacy, rated on a five-point scale from not confident (1) to extremely confident (5), and satisfaction, were evaluated via surveys before the first and after the final session. During the follow-up session, participants individually practiced their MI skills with trained standardized patients (SP) in ten-minute sessions. All sessions were video recorded and coded to assess MI proficiency. Data were analyzed using descriptives and t-tests, and Motivational Interviewing Treatment Integrity (MITI) 3.1.1 was used to assess MI proficiency. Results: All 13 participants identified as non-Hispanic, White, and were seniors in an undergraduate nursing program, with a mean age of 21.6 ± 1.6. After the pilot, there was a significant mean increase ( P = 0.003) in nutrition knowledge (score out of 24; pre: 18.6 ± 2.1, post: 20.5 ± 2.5). There was also a mean increase in self-efficacy (pre: 3, post: 4), and nine participants obtained beginning MI proficiency in at least one category, showing success relative to the training time they received. Most participants reported being very (63.6%) or extremely (9.1%) satisfied with the curriculum and training. They provided useful feedback about changes before future use of the curriculum. Conclusions: The pilot succeeded in improving knowledge and self-efficacy related to MI, but some changes are required to improve the curriculum for future use. Given the important role nurses play in school and healthcare settings, finding ways to incorporate obesity prevention is crucial. Funding Sources: This work is supported by the Rhode Island EOHHS Health Care Workforce Transformation Project.